Implementing the global women, peace and security agenda in Ethiopia, Kenya and Mali - Karmen Tornius; Marie Kolling; Lars Engberg-Pedersen (Danish Institute for International Studies (DIIS), 2023)
This report examines how and to what extent national action plans (NAPs) are a useful tool for fostering local ownership of the women, peace and security (WPS) agenda. Focusing on three case countries, Ethiopia, Kenya and Mali, the report interrogates different actions that can generate ownership and how these manifest in institutional approaches to WPS or UNSCR 1325 adoption and implementation. The three countries present very different circumstances for engaging with the WPS agenda and for doing so through NAPs. The report shows that the WPS agenda is also implemented by civil society beyond the scope of NAPs, while the narrow purview of actors involved with NAPs has led to limited ownership by government and civil society actors beyond those directly involved. NAP implementation is further challenged by unsustainable funding strategies and while diverse actors engage with WPS in their localities, a lack of data and reporting limits the monitoring of NAP implementation. Notwithstanding these limitations, the drafting and adoption of NAPs can link the work people do on the ground to official government policy and thereby legitimise the WPS work of different stakeholders who can mobilise around WPS NAPs strategically. NAPs are also used to monitor governments' engagement with the agenda, to mobilise funds and to debate the gendered aspects of new and old security challenges and gender equality more broadly, all of which can facilitate holding governments to account and advancing the WPS agenda.
Keywords: 300; Women; peace and security; WPS; National action plan; NAP; Kenya; Ethiopia; Mali; UNSCR 1325